Stimulasi Verbal Linguistik Anak Melalui Metode Bermain Peran - Sakinah Siregar (BUHUTS AL-ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2021)
ABSTRACTThis study aims to determine the verbal linguistic development of young children through the application of the role playing method. This research was conducted based on the findings of the low verbal linguistic intelligence of children due to lack of interaction with teachers and peers this is due to the dominant learning activity of calistung and the use of learning methods that are less effective in stimulating all aspects of children's development, especially children's verbal linguistics. The research design used was a post test only control design, using two groups that had the same characteristics. While the determination of the class is done randomly with a total sample of 33 children in each group. The instrument of data collection was observation with t-test data analysis. . With a significance level of = 0.05. Based on these results, the hypothesis states that stimulation using the role playing method has a significant effect on children's verbal linguistics, namely from the results of hypothesis testing, it is obtained that tcount t table is 11.39 1.671 at level = 0.05. Thus the role playing method has a significant effect on the development of verbal linguistic intelligence in early childhood.Keywords: verbal linguistics, role playing, early childhood.